2018
DOI: 10.3390/nu10010076
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Associated Impact of Early Leucine Supplementation on Adult Predisposition to Obesity in Rats

Abstract: Early nutrition plays an important role in development and may constitute a relevant contributor to the onset of obesity in adulthood. The aim of this study was to evaluate the long-term impact of maternal leucine (Leu) supplementation during lactation on progeny in rats. A chow diet, supplemented with 2% Leu, was supplied during lactation (21 days) and, from weaning onwards, was replaced by a standard chow diet. Then, at adulthood (6 months of age), this was replaced with hypercaloric diets (either with high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…However, insulin may be needed for the Leu-induced in vivo stimulation of protein synthesis in skeletal muscles [ 49 ]. Apart from skeletal muscle, Leu also enhances protein synthesis in other tissues such as adipose tissue [ 50 ]. Ile or Val alone has no effectiveness as a nutrient regulator of protein synthesis in skeletal muscles [ 48 ].…”
Section: Roles Of Bcaas In Nutrition Metabolismmentioning
confidence: 99%
“…However, insulin may be needed for the Leu-induced in vivo stimulation of protein synthesis in skeletal muscles [ 49 ]. Apart from skeletal muscle, Leu also enhances protein synthesis in other tissues such as adipose tissue [ 50 ]. Ile or Val alone has no effectiveness as a nutrient regulator of protein synthesis in skeletal muscles [ 48 ].…”
Section: Roles Of Bcaas In Nutrition Metabolismmentioning
confidence: 99%
“…This is a possible speculation why leucine influence insulin secretion and then further affect the risk of DN. In other studies, it was found that the supplement of lacto-leucine during lactation take the change of insulin levels in the offspring which were affected by gender (28). This difference may be caused by that the activation of the mTOR pathway and the ribosomal kinase S6K1 showed a higher expression in female (39,40).…”
Section: Discussionmentioning
confidence: 93%
“…A study found that the supplement of leucine in diet can active the AMPK (26), which was considered as a newly identified regulator of renal hypertrophy in diabetes (26,27). Higher plasma leucine has been found to reverse the disorder of tricarboxylic acid (TCA) cycle metabolism and carnitine metabolic disorders in mice with DN (28,29). Hyperlipidemia is also a common cause of DN, and the supplementation of leucine in animal tests can reduce blood lipid (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leucine administration in premating rat dams has been explored to show its relation to improving the litter birth weight, as well as the improvement of the dams’ immune function and antioxidative capability [ 13 ]. In addition, concerning a possible leucine influence on insulin and glucose homeostasis, some studies reported that leucine supplementation during lactation in Wistar rats could improve the dams’ body composition, without compromising the offspring growth, and other studies referred to the predisposition to the obesity in adult offspring [ 14 , 15 ]. In this way, our study focused on the understanding of the metabolic responses provided by a maternal leucine-rich diet which minimized the muscle mass loss in tumor-bearing adult offspring.…”
Section: Introductionmentioning
confidence: 99%